Perceptions of Engineering students, lecturers and academic development practitioners about academic development classes at a university of technology (Journal of Student Affairs in Africa, 2021)
With the increase in student enrolments in higher education, which has resulted in changes to student profiles, academic development has become important in terms of students’ success. This article is a report on a qualitative study that used in-depth interviews to investigate the perceptions of Engineering students and staff to academic development classes at a university of technology (UoT) in South Africa. The students’ feelings concerning the need for academic development to continue beyond their first year of study was of particular interest. Participants included five lecturers from the Engineering faculty and four academic development practitioners, who were all purposefully selected. The sample consisted of men and women who were interviewed individually. Interviews were also conducted with ten first-year Engineering students and ten second-year students, who were randomly selected on the grounds of having been involved in the academic development programme during their first year. The responses of the lecturers were compared with those of the academic development practitioners and the first- and second-year students’ responses were compared. It emerged that academic development was considered questionable as it did not seem to be structured and that the academic development curriculum, itself, was problematic.
Keywords: Academic development; engineering education; scaffolding; self-regulated learning; students